Pembuatan desain batik motif jlamprang menggunakan aplikasi ibis paint x sebagai dasar perencanaan produksi - Maulidia, Hana; Murty, Daru Anggara; Sasongko, Aditya Dimas Wahyu (Canting : Jurnal Batik Indonesia, 2024)
When making batik designs, you must be able to utilize the latest technology. Mobile phones are a vital necessity for human life. This must be utilized in the process of creating digital batik designs. Ibis Paint X can be used as a basis for production planning in digital batik designs with jlamprang motif. This research is qualitative research where the data is presented in the form of descriptions and pictures. Each stage of design creation is documented in the form of images and videos. The data collection methods used are observation, observation, literature study and documentation methods. Every batik production process must go through a planning process which aims to achieve production efficiency. The digital batik designs that have been created are used as a basis for planning batik production starting from the preparation process, wax gluing, coloring and wax removal. The entire process can be identified in advance with this digital batik design. Because the estimated results to be achieved have already been determined. This certainly makes it easier for craftsmen to determine production costs and estimated processing time.